Handbook of Labor, Human Resources and Population Economics 2021
DOI: 10.1007/978-3-319-57365-6_204-1
|View full text |Cite
|
Sign up to set email alerts
|

Unions, Collective Bargaining, and Firm Performance

Abstract: The impact of unions on firm performance has been the subject of debate and controversy in most industrialized countries, particularly in the United States and the United Kingdom. The purpose of this chapter is to review and assess the scope and limitations of the economic analysis of unions as well as the controversies surrounding the conclusions of existing empirical research. Although it is difficult to draw firm and general conclusions on the effects of unions on firm performance, the existing results lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 113 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…According to Tripti and Ginni (2015), UI is the perceived advantage of union membership on traditional work conditions, such as salaries and fringe benefits, as well as non-traditional work conditions, such as JS etc. Prior studies have established a connection between union activities and other positive and negative behaviours, such as increased productivity, absenteeism and turnover (Erlina & Hakimah, 2020;Kim, 2019;Laroche, 2020). These and similar studies have found that active union membership facilitates collective bargaining, which improves working conditions, fringe benefits, job satisfaction, and employee or organisational commitment, and, as a result, lowers turnover intentions, absenteeism, and other unproductive behaviour (Deery et al, 2014;Olonade et al, 2020;Zacharewicz et al, 2016).…”
Section: Perceived Union Instrumentality and Workplace Deviancementioning
confidence: 93%
See 1 more Smart Citation
“…According to Tripti and Ginni (2015), UI is the perceived advantage of union membership on traditional work conditions, such as salaries and fringe benefits, as well as non-traditional work conditions, such as JS etc. Prior studies have established a connection between union activities and other positive and negative behaviours, such as increased productivity, absenteeism and turnover (Erlina & Hakimah, 2020;Kim, 2019;Laroche, 2020). These and similar studies have found that active union membership facilitates collective bargaining, which improves working conditions, fringe benefits, job satisfaction, and employee or organisational commitment, and, as a result, lowers turnover intentions, absenteeism, and other unproductive behaviour (Deery et al, 2014;Olonade et al, 2020;Zacharewicz et al, 2016).…”
Section: Perceived Union Instrumentality and Workplace Deviancementioning
confidence: 93%
“…Many empirical studies have found a direct correlation between UI and JS among unionised workers (Benitez, 2020;Hipp & Givan, 2015;Shan et al, 2016). Various of these studies found a link between unionism and some measures of job satisfaction, albeit the connection is dependent on the labour relations climate (Donegani & Mckay, 2012;Laroche, 2020) and the strength of the relationship, which, according to Hipp and Givan (2015), varies by country. While results vary by country, an analysis of 18 countries that took part in the large-scale European Social Survey between 2006 and 2010 found that trade union members typically express higher rather than lower JS than nonunion members and that as a result of unionism and the collective bargaining process, job security, job satisfaction, and public value increase, while voluntary turnover decreases (Budd, 2014;Donegani & Mckay, 2012).…”
Section: Union Instrumentation and Job Satisfactionmentioning
confidence: 99%
“…Freeman (1976) and Freeman and Medoff (1984) claim that by providing workers with a means of expressing discontent through a collective voice, unions can reduce turnover and improve morale, motivation, job satisfaction and cooperation, thereby enhancing productivity. The additional information provided by a collective voice can moreover enable firms to choose a better mix of working conditions, workplace rules and wage levels (Laroche, 2020). In Norway, for example, the management and the union in firms participating in collective agreements can agree on more flexible working time arrangements than are otherwise permitted by law.…”
Section: Related Literaturementioning
confidence: 99%
“…The mixed evidence on what unions do to productivity calls for the scope of union research to extend to more countries, sectors, time periods and institutional contexts (Laroche, 2020). Unions operate in very diverse environments with respect to how institutions and legislation regulate and facilitate their activities and organization.…”
Section: Introductionmentioning
confidence: 99%
“…Although strikes have long been topics in industrial relations and labor economics, empirical interest in them has waned with the withering away of the strike, even if strike models can be tasked with explaining strike evanescence as well as resurgence (Kaufman, 1982;Campolieti, 2021). Meantime, there has been heightened interest in the potential contribution of the quality of labor relations to firm performance outcomes (Laroche, 2021) and indeed unemployment (Blanchard and Philippon, 2004). One aim of the present treatment is to seek to narrow this 'gap' by taking advantage of the most recent European Company Survey (ECS) for 2019.…”
Section: Introductionmentioning
confidence: 99%